OPTIMIZING THE ROLE OF THE VILLAGE CONSULTATIVE BODY IN MONITORING THE PERFORMANCE OF THE VILLAGE HEAD IN BUATA VILLAGE, BOTUPINGGE SUB-DISTRICT, BONE BOLANG REGENCY: OPTIMIZING THE ROLE OF THE VILLAGE CONSULTATIVE BODY IN MONITORING THE PERFORMANCE OF THE VILLAGE HEAD IN BUATA VILLAGE, BOTUPINGGE SUB-DISTRICT, BONE BOLANG REGENCY - Tirani Mantulangi; Darman (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This study aims to determinate the opmizating of the role the Village Deliberation Agency (BPD) in Supervising the performance of the Village Head in Buata Village, Botunpingge District, Bone Bolango Regency. This research method used a qualitative research approach with a qualitative research design because it focuses on several aspect in the form of interviews, open data collection, and document collection. This research was carried out at yhe Buata Village Office, Botupinge District, Bone Bolango regency, for 2 moths and 2 weeks from Ari 17, 2023 – Juni 26, 2023. Optimizing the Role of the Village Deliberation Agency (BPD) in Supervising the Performance of the Village Head in Buata Village shows that its performance is quite good seen from the perspective of BPD in responding to serious matters such as complaints and aspirations from the community and also how to cooperate between the BPD, the Village Head, and also the Village Government in proposing the development of a Village Deliberation Agency in Buata Village, Botupingge District, Bone Bolango Regency, is well implemented. However it still needs attention from the regional Government so that the performance of the BPD can be Improved.